Impact of extracellular vesicles on innate immunity. Issue 6 (December 2019) - Chen, Zhizhao; Larregina, Adriana T.; Morelli, Adrian E.
Abstract : Purpose of review: Extracellular vesicles released by prokaryote or eukaryote cells are emerging as mechanisms of cell-to-cell communication, by either physically interacting with the surface of target cells or transferring proteins/peptides, lipids, carbohydrates, and nuclei acids to acceptor cells. Accumulating evidence indicates that extracellular vesicles, among other functions, regulate innate and adaptive immune responses. We revisit here the effects that extracellular vesicles of various origins have on innate immunity. Recent findings: Extracellular vesicles comprise a heterogeneous group of vesicles with different biogenesis, composition and biological properties, which include exosomes, microvesicles, apoptotic cell-derived extracellular vesicles, and other extracellular vesicles still not well characterized. Extracellular vesicles released by pathogens, leukocytes, nonhematopoietic cells, tumor cells, and likely allografts, can either stimulate or suppress innate immunity via multiple mechanisms. These include transfer to target leukocytes of pro-inflammatory or anti-inflammatory mediators, membrane receptors, enzymes, mRNAs, and noncoding RNAs; and interaction of extracellular vesicles with the complement and coagulation systems. As a result, extracellular vesicles affect differentiation, polarization, activation, tissue recruitment, cytokine and chemokine production, cytolytic and phagocytic function, and antigen transfer ability, of different types of innate immune cells. Summary: The field of intercellular communication via extracellular vesicles is a rapid evolving area and the effects of pathogen-derived and host-derived extracellular vesicles on innate immunity in particular, have received increasing attention during the past decade. Future studies will be necessary to assess the full potential of the crosstalk between extracellular vesicles and the innate immune system and its use for therapeutic applications to treat chronic inflammation-based diseases and cancer growth and dissemination, among the growing list of disorders in which the innate immune system plays a critical role.